1978
DOI: 10.1111/j.1365-2028.1978.tb00436.x
|View full text |Cite
|
Sign up to set email alerts
|

Social biology of bushbuck (Tragelaphus scriptus Pallas 1776) in the Nairobi National Park, Kenya

Abstract: Summary A study to investigate some aspects of the social biology of bushbuck (Tragelaphus scriptus Pallas 1776) was carried out in a 2.59 km2 study area in the Nairobi National Park, Kenya. Observations throughout 1966 using binoculars and photography identified thirty‐one male and thirty‐three female bushbuck. Together with an estimated fourteen juveniles, the density in the study area was 30.1/km2. Distribution is aggregated with loose family groups concentrating around forest edge areas near to dams or riv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 15 publications
4
17
2
Order By: Relevance
“…Except for Wilson and Child (1964), who observed bushbuck only during the dry season, all other authors did not distinguish between seasons (Allsopp 1978;Elder and Elder 1970;Odendaal and Bigalke 1979). To keep data comparable to other previous studies, group size records were expressed as the mean group size (MGS) and typical group size (TGS; Jarman 1974; sensu Reiczigel et al 2008: crowding).…”
Section: Methodsmentioning
confidence: 92%
“…Except for Wilson and Child (1964), who observed bushbuck only during the dry season, all other authors did not distinguish between seasons (Allsopp 1978;Elder and Elder 1970;Odendaal and Bigalke 1979). To keep data comparable to other previous studies, group size records were expressed as the mean group size (MGS) and typical group size (TGS; Jarman 1974; sensu Reiczigel et al 2008: crowding).…”
Section: Methodsmentioning
confidence: 92%
“…GGNP baboons always encountered their mammalian prey opportunistically, typically while foraging. Bushbuck infants, at least in Kenya, spend time in concealment away from their mothers during the first few weeks of life [Allsopp, 1978;see also Waser, 1975]. Infant parking while mothers forage is also likely a regular occurrence at GGNP, at least for red-flanked duiker, because observers never encountered mothers with babies ( table 2 ; neonates of blue and yellow-backed duiker were likewise never seen).…”
Section: Prey Acquisitionmentioning
confidence: 99%
“…Recent studies have shown that male home ranges encompass the home ranges of several females, and males use the inner core of their home ranges almost exclusively . Previously, territoriality was thought to be absent in bushbuck (Allsopp 1978;Waser 1975a;Estes 1991a), or evidence for territoriality was at least uncertain (Verheyen 1955;Walther 1964;Jacobsen 1974;Owen-Smith 1976;Odendaal and Bigalke 1979). Aggressive behaviour may therefore be important in the context of territorial defence.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 97%
“…Aggressive and submissive displays serve important functions during territorial behaviour, at least in the male sex: Formerly, bushbuck were thought to lack territoriality (Allsopp 1978;Waser 1975a;Owen-Smith 1976;Odendaal and Bigalke 1979;Estes 1991a). Recent studies, however have shown that bushbuck males use the inner core of their home range exclusively and defend the inner core more vigourously against intruders than against peripheral parts (Wronski 2004).…”
Section: Agonistic Behaviourmentioning
confidence: 98%
See 1 more Smart Citation